2002
DOI: 10.4192/1577-8517-v2_3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Internet for Corporate Reporting by Spanish Companies

Abstract: Abstract. During the last decade there has been a profound revolution in the information technology by means of the Internet, and obviously accounting has been directly affected by this change. Although the main objective of this paper is to study the use of the Internet by Spanish companies to disclose financial information, we also discuss about the reasons of companies to use the new technologies to communicate with interested parties and its consequences. The empirical research is based on companies listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 10 publications
7
95
0
15
Order By: Relevance
“…Cormier, Ledoux and Magnan (2009: 8) reported a negative association. The following studies, however, reported no significant association: Aly et al (2010: 191), Bollen et al (2006: 291), Debreceny et al (2002), Froidevaux (2004), Almilia (2009: 95), Larrán and Giner (2002), and Oyelere et al (2003).…”
Section: Leveragementioning
confidence: 96%
See 1 more Smart Citation
“…Cormier, Ledoux and Magnan (2009: 8) reported a negative association. The following studies, however, reported no significant association: Aly et al (2010: 191), Bollen et al (2006: 291), Debreceny et al (2002), Froidevaux (2004), Almilia (2009: 95), Larrán and Giner (2002), and Oyelere et al (2003).…”
Section: Leveragementioning
confidence: 96%
“…On the other hand, Ashbaugh et al (1999), Ettredge et al (2002: 366), Marston and Polei (2004), Oyelere et al (2003), Pirchegger and Wagenhofer (1999) (German sample), Xiao et al (2004: 215), Larrán and Giner (2002), Abdelsalam, Bryant and Street (2007), Bollen et al (2006: 291), Cormier et al (2009) and Leventis and Weetman (2004) all document no significant association between financial performance and disclosure.…”
Section: Financial Performancementioning
confidence: 97%
“…Estudos que caracterizam a realidade de um determinado país (Salawu, 2013); (Pervan, 2005); (Silva & Filho, 2005); (Barak, 2004); (Marston & Polei, 2004); (Xiao, Yang, & Chow, 2004); (Larran & Giner, 2002); (Marston, 2003); (Pérez & Delgado, 2002); (Silva & Quaresma, 2001); (Craven & Marston, 1999); (Hedlin, 1999) Estudos que fazem algum tipo de comparação entre empresas ou países (Alves, 2005); (Barak, 2004); (Marston & Polei, 2004); (Geerings, Bollen, & Hassink, 2003); (Craven & Marston, 1999); (Deller, Stubenrath, & Goethe, 1999); (Pirchegger & Wagenhofer, 1999); (Westarp, Dieter, Stubernat, Buxmann, & Konig, 1999) Estudos ou documentos que contemplam recomendações (Dominguez & Gallego, 2006); (Smith & Pierce, 2005); (Fisher, Oyelere, & Laswad, 2004); (León, 2003); (Debreceny, Gray, & Mock, 2001); (Lymer, 1999); (Lymer, Debreceny, Gray, & Rahman, 1999); (Oyelere, Laswad, & Fisher, 2003); (Westarp, Dieter, Stubernat, Buxmann, & Konig, 1999); (Quagli & Riva, 2005); (Beattie & Pratt, 2003) …”
Section: Tema Autoresunclassified
“…Hackston & Milne (1996), por su parte, sostienen que una vez alcanzados los objetivos económicos, las empresas tienden a aumentar su inversión en actividades de tipo social. Por tanto, las empresas con resultados económicos positivos son más proclives a divulgar información de todo tipo, entre la que se destaca la información sobre RSC (Larrán & Giner, 2002;Marston & Polei, 2004). En línea con la literatura existente, la tercera hipótesis planteada es la siguiente: H3: La rentabilidad financiera de las empresas farmacéuticas influye positivamente en la divulgación de información sobre RSC.…”
Section: Rentabilidad Financieraunclassified
“…En este caso la relación es positiva, por lo que se confirma la relación esperada. Así, tal y como se indicó antes, las empresas con mejores resultados están más dispuestas a utilizar mecanismos voluntarios de información, entre los que se encuentra la divulgación de información sobre sostenibilidad (Archel & Lizarraga, 2001;Larrán & Giner, 2002;Marston & Polei, 2004).…”
Section: A R T í C U L O S O R I G I N a L E Sunclassified